Isolation and Characterization of a Water-soluble Disaccharide from Methanolic Extract of Arisaema utile and Its Evaluation for Antioxidant and Antifungal Activity: Isolation and Characterization of a Water-soluble Disaccharide from Methanolic Extract of Arisaema utile and Its Evaluation for Antioxidant and Antifungal Activity - Bhat, Arif Hussain (International Journal of Pharmaceutical & Biological Archive, 2019)
The aim of this study is to isolation, identification and characterized the bioactive compounds from the rhizomes of Arisaema utile. Preliminary phytochemical screening of the rhizome extract of A. utile revealed the presence of steroids, terpenoids, flavonoids, alkaloids, saponins, carbohydrates, and fatty acids. The air-dried rhizomes were pulverized to a powder, subjected to Soxhlet extraction and compound isolation. The isolated compound was colorless crystalline, which was further subjected to IR,13CNMR, and 1HNMR for proper characterization and elucidation of the structure. The compound was concluded as water-soluble disaccharide–Sucrose (2R,3R,4S,5S,6R)-2-[(2S,3S,4S,5R)-3,4-dihydroxy-2,5-bis(hydroxymeth-yl)oxolan-2-yl]oxy-6-(hydroxymethyl)oxane-3,4,5-triol, antioxidant activity of the isolated compound was measured by 2,2-Diphenyl-1-picrylhydrazyl assay under in vitro condition. The isolated compound showed the most promising radical scavenging activity at a concentration of 10 μg/ml. Antifungal activity of the isolated compound was investigated against five fungal strains (Candida albicans, Candida glabrata, Candida paropsilosis, Candida tropicalis, and Candida krusei), using MIC80 assay. The most susceptible strains were Candida paropsilosis (MIC80 = 128 μg/mL).